PENGARUH KOMPONEN CITRA PERUSAHAAN TERHADAP KEPUTUSAN PEMBELIAN PADA BENGKEL BERKAH MOTOR DI TENGGARONG - Lukas, Julius; Johansyah; Aryani, Farida (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2023)
The purpose of this research is to find out the component variables of the company's image including store location, product, price, customer service and physical facilities have a significant influence on purchasing decisions at Bengkel Berkah Motor in Tenggarong. This study uses a quantitative descriptive analysis method, with a focus on assessing Store Image and purchasing decisions. The data used are data from the distribution of questionnaires that are considered relevant. Based on these data, the indicators of the research variables were calculated using analytical tools according to theoretical principles. The data collection technique in this study was carried out randomly to obtain a sample from the population in question, in order to obtain good data, it was selected using the questionnaire and documentation method. This research will be carried out for 1 (one) month (30 days) estimated in July 2020 who will come to the Berkah Motor Workshop as many as 97 consumers. To determine the effect of the independent variable on the dependent variable, multiple linear regression analysis was used. From the results of the study, the results obtained in this study are that the variables of Store Image Components including Store Location, Product, Price, Customer Service and Physical Facilities Have an Influence on Purchase Decisions at the Berkah Motor Workshop in Tenggarong